Simulated atmospheric nitrogen deposition inhibited the leaf litter decomposition of Cinnamomum migao H. W. Li in Southwest China - Xiao-Long Huang; Jing-Zhong Chen; Deng Wang; Ming-Ming Deng; Meng-Yao Wu; Bing-Li Tong; Ji-Ming Liu (Scientific Reports, 2021)
Abstract Atmospheric nitrogen (N) deposition could affect various ecological processes in forest ecosystems, including plant litter decomposition and nutrient cycling. However, the mechanism of underlying litter decomposition and nutrient cycling of Cinnamomum migao under N deposition remains unclear. Therefore, we conducted a simulated N deposition experiment including four onsite treatments to assess the effects of N input on C. migao leaf litter decomposition, nutrient release, and soil enzyme activity. The results showed that simulated N deposition significantly increased the amount of total residual mass and lignin and cellulose, decreased the decomposition rate, and suppressed net nutrient release. N input increased C, N, and P ratios as decomposition progressed, and the proportion of mass remaining was positively correlated with the proportions of lignin and cellulose remaining at the later stage of decomposition. The differences in soil enzyme activity were primarily due to enzyme type and sampling time. We conclude that simulated N deposition significantly suppressed the leaf litter decomposition of C. migao by mainly altering the chemical properties and suppressing the decomposition of the organic matter in leaf litter. Lignin might have played an important role in the loss of leaf litter biomass at the later stage of decomposition.